Pengembangan Estetika Melalui Kegiatan Cooking Class di RA As-Shofa Ciparay - Heri Hidayat; Nadia Nuraziani; Qolbiatum Mutmainah; Silva Inten Sulistya (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
This study examines how cooking class plays a role in the development of aesthetic attitudes in early childhood with the aim of this study is to improve and develop aesthetic attitudes of early childhood. The data collection process was carried out by interviewing related teachers through Whatsapp media accounts and analyzing learning videos. The type of research used is descriptive research with a quantitative approach. The subject in this study is the child of RA As-Shofa class b. Interviews were conducted with educators about the cooking class learning model and how the learning was carried out. The development of aesthetics through cooking class activities at RA As-Shofa for grade b children makes children feel more confident in showing their aesthetic attitudes.